Visceral Adipose Tissue Influence on Health Problem Development and Its Relationship with Serum Biochemical Parameters in Middle-Aged and Older Adults: A Literature Review - Vanessa C. Moreira; Calliandra M. S. Silva; Alexis F. Welker; Izabel C. R. da Silva (Journal of Aging Research)
Background. The amount of visceral adipose tissue (VAT) tends to increase with age and is associated with several health problems, such as cardiometabolic diseases, increased infections, and overall mortality. Objectives. This review provides a general assessment of how visceral adiposity correlates with the development of health problems and changes in serum biochemical parameters in middle-aged and older adults. Methods. We searched specific terms in the Virtual Health Library (VHL) databases for VAT articles published in the English language between 2009 and 2019 related to older adults. Results. The search found twenty-three publications in this period, of which nine were excluded. The publications had a population aged between 42 and 83 years and correlated the VAT area ratio with several comorbidities (such as pancreatitis, depression, cancer, and coronary heart disease) and serum biochemical parameters. Conclusion. Further research on the association between visceral obesity and the emergence of health problems and the relationship between VAT and changes in serum biochemical parameters in older individuals should deepen the understanding of this connection and develop preventive actions.